OBSERVATION OF THE 1S-2S TRANSITION IN ATOMIC-HYDROGEN IN AN ATOMIC-BEAM - Foot, C; Hannaford, P; Stacey, D; Thompson, C; Woodman, G; Baird, P; Swan, J; Woodgate, G (1990)
The authors report the observation of the 1S-2S two-photon transition in atomic hydrogen in an atomic beam, excited by light from a narrow-band continuous-wave laser. The excitation takes place in a collision-free environment and detection of the resonance is carried out by Stark-quenching the metastable atoms some distance from the interaction region. This approach removes the limitations of cell excitation employed in previous experiments with continuous-wave lasers, and should allow the full precision of modern tunable laser techniques to be applied to the 1S-2S transition. It also gives a new method for producing a collimated beam of metastable atoms which has particular applications to a variety of future experiments with cold hydrogen.